Prospects from Diagnosis to Treatment in Cancer Using Magnetic Methods - Kusakabe, Moriaki; Kuwahata, Akihiro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Many cancer diagnosis and treatment modalities have been developed over time, among which radioisotopes have been widely used. Recently, with the application of magnetic nanoparticles, a wide range of non-invasive diagnosis and treatment methods using magnetic techniques have attracted attention. This Special Issue introduces a lymph node biopsy method with a magnetic probe for the treatment of cancer, rapid immunostaining using magnetic nanoparticles in pathological diagnosis, cancer imaging with MRI (magnetic resonance imaging)/MPI (magnetic particle imaging), magnetic hyperthermia for cancer treatment, and the development of magnetic nanoparticles.